Sustainable business model innovation and ESG performance in the South African mining industry - Nhlanhla, Khulekani (University of the Witswatersrand, Johannesburg, 2023)
The purpose of this study is to investigate the influence of ESG (environmental, social, and governance) performance on sustainable business model innovation in the South African mining industry. The study is conducted with the aim to understand which of the ESG factors are most influential in driving sustainable business model innovation and how they either support or hinder innovation. Due to its extractive nature, and natural resources and reserves mostly being located in countries of the global south (emerging economies) like South Africa, the mining industry has been known to have high impacts on the environment and society (Krause & Drusche, 2021). The industry therefore has a profound role to play in sustainable development and addressing social and environmental challenges (Krause & Drusche, 2021). The nature and direction of the relationship between ESG and sustainable business models has been researched to a certain extent in industries like finance, but the studies are skewed towards regions such as Europe and generalised to other regions like Africa. In a study by Spoz et al., (2021), the authors claim that the study analysed the results from an international context (Asia, America, Africa, and Europe), but only make mention of Europe and Asia, with an emphasis on Europe in their study. Of the three ESG factors (environment, social and corporate governance), the study showed that there’s a moderately strong relationship for a positive impact between social factors and sustainable business models (SBMs) in Europe (Spoz et al., 2021). In a similar study conducted by Ritala et al., (2018) on United States companies listed in the S&P (Standard and Poor’s) 500 index, the researchers found that a significant number of firms adopted environmentally oriented sustainable business models (SMB) more frequently than those oriented toward society. Available literature does not sufficiently make a link between environmental, social and governance performance and sustainable business model innovation applied in the mining industries of emerging economies like South Africa. Neglecting the link ii between ESG performance and sustainable business model innovation in regions like South Africa and its mining industry poses risks of environment degradation, regulatory setbacks, and missed economic opportunities (Quayson, et al., 2023). This research has examined how ESG performance supports or thwarts sustainable business model innovation in the South African mining industry. Through the collection of data using two approaches, semi-structured interviews, and the examination of publicly available company documentation such annual ESG and sustainability reports, this study found that in the South African mining industry, the governance factor was most influential in decisions regarding innovation and sustainable business model innovation. Within the governance factor, elements such as policy and regulation stood out as elements that drove the governance factor. This came from inefficiencies caused by uncertainty in regulation and policy which in turn cause delays in issuing of licenses and permits for innovations or innovative projects needed by the mining industry. Sustainable development and business model innovation require a systematic approach emphasizing an equal level of importance on all the three factors: social, environmental, and governance within the ESG framework. Active adaptive management can be used to implement proactive monitoring, experimentation, and iterative implementation of actions in pursuit of improved ESG performance that has a positive impact on sustainable business model innovation.
A research proposal submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in the field of Innovation Studies
Keywords: ESG (environmental, social, and governance); Sustainable business model innovation; Mining industry; Natural resources; Environmental challenges; UCTD; SDG-8: Decent work and economic growth